Local Government and Community Efforts in the Development of Kalaodi Agrotourism, Tidore Archipelago City, Indonesia - Kader, Abdurrahman (Graduate School, Universitas Brawijaya, 2021)
This research aimed to examine the development of Kalaodi Agrotourism, the development of tourism facilities in the Kalaodi Agrotourism area, and the development of human resources in the tourism sector carried out by local governments and communities. This research used a qualitative descriptive approach, and it used an interactive model as the data analysis technique. The results showed that Kalaodi had many kinds of tourism wealth, specifically, in the form of nature, agro, and cultural tourism. The Kalaodi community had the will and enthusiasm to develop tourism objects in their area. There were various public transportation facilities such as roads, good sanitation, electricity facilities, and communication facilities even though Kalaodi was a village located far from the central government and urban areas. In addition, the Kalaodi community had developed human resource development programs, such as the creation of literacy houses, the formation of art galleries, English language training, and home industry product development training. In developing agrotourism, the collaboration between the local government and the community is needed, both in the development of tourist objects and tourism support facilities.Keywords: Development, Kalaodi Agrotourism, Tidore